Synthesis and characterization of hexahydropyrimidines and their new derivatives - Hamed, Shukkur A.; Thaker, Athraa; Rudaini, Bilal Majid; Naeem, Hasanain Salah; Muntaz Abu Bakar; Siti Aishah Hasbullah (Penerbit Universiti Kebangsaan Malaysia, 2024)
Three new hexahydropyrimidine derivatives 1a – 1c were successfully synthesized using the Mannich-type reaction. Furthermore, the synthesis of three amino bases 2a – 2c was achieved through the reduction reaction of pyrimidine compounds using hydrazine, followed by the substitution reaction of nitro groups at diverse positions. Subsequently, one of the synthesized amino base derivatives 2c underwent conversion into seven Schiff bases 3a – 3g via a condensation reaction involving the aforementioned amino base derivative and a selection of benzaldehyde derivatives. Four amide compounds 4a – 4d have been synthesized by a reaction of the secondary amine group in the pyrimidine ring with benzoyl chloride. The products were subjected to comprehensive characterization employing rigorous analytical techniques, including FT-), 1 H-NMR (Proton Nuclear Magnetic Resonance Spectroscopy), and LC-MS (Liquid Chromatography–Mass Spectrometry). Additionally, the Molecular Electrostatic Potential (MEP) study was carried out to further investigate the properties of the synthesized compounds. The yields of the three methods used to synthesise new hexahydropyrimidine derivatives varied depending on the specific substituents added to the aromatic ring.